2018
DOI: 10.1109/jbhi.2017.2668993
|View full text |Cite
|
Sign up to set email alerts
|

HyCLASSS: A Hybrid Classifier for Automatic Sleep Stage Scoring

Abstract: Automatic identification of sleep stage is an important step in a sleep study. In this paper, we propose a hybrid automatic sleep stage scoring approach, named HyCLASSS, based on single channel electroencephalogram (EEG). HyCLASSS, for the first time, leverages both signal and stage transition features of human sleep for automatic identification of sleep stages. HyCLASSS consists of two parts: A random forest classifier and correction rules. Random forest classifier is trained using 30 EEG signal features, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(59 citation statements)
references
References 41 publications
0
59
0
Order By: Relevance
“…Quality of life is a primary indicator of good life (Li et al, 2017). Individual health factors and satisfaction in life would influence physical and mental health, social economy, and family conditions.…”
Section: Quality Of Lifementioning
confidence: 99%
See 2 more Smart Citations
“…Quality of life is a primary indicator of good life (Li et al, 2017). Individual health factors and satisfaction in life would influence physical and mental health, social economy, and family conditions.…”
Section: Quality Of Lifementioning
confidence: 99%
“…Lin (2016) indicated that medical education allowed college students having further cognition of self-health concept to reflect on the physiological, psychological, and social perception of quality of healthy life and effectively enhance quality of life. Cheng (2015) mentioned that medical education could enhance health competency and further affect health, family, and even expenditure for health insurance (Li et al, 2017). Caldwell et al (2016) pointed out the large effect of health competency on quality of life; especially, changing physical and mental health with lifestyles presented great influence on quality of life, and medical education would enhance useful concepts and strategies for people.…”
Section: H2mentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, it has inspired scientists to create programmed sleep organize arrangement frameworks that can effectively perform PSG sleep investigation. As of late, an assortment of strategies has been explored for the grouping of sleep stages utilizing the PSG information [2], [3]. To total and…”
Section: Iintroductionmentioning
confidence: 99%
“…However, many sleep disorders, such as insomnia, apnea, and narcolepsy, disturb sleep quality and thus threaten human health [3]. Effective diagnosis and treatment of these sleep disturbances rely on accurate detection of sleep and sleep cycles [4]. Therefore, sleep stage classification is a premise and significant step for sleep analysis.…”
mentioning
confidence: 99%